Catharsis - The Real Effects of Bank Insolvency and Resolution - Josef Korte (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2013)
In general, banks play a growth-enhancing role for the real economy. However, distorted incentives of banks, depositors, and regulators around bank insolvency may corrupt banks' credit allocation and monitoring decisions, leading to suboptimal real economic outcomes. A rules-based prompt resolution regime for insolvent banks may reestablish the incentive system and provide for economically superior credit allocation and monitoring. We test this hypothesis of a 'catharsis effect' of regulatory insolvency using a large firm-level dataset and proposing a new indicator to measure the catharsis effect. Employing an instrumental variable setup and an interaction approach, we try to overcome potential endogeneity and causality concerns usually inhering research on real economic implications of bank regulation. We find a comparably stronger implementation of a hypothetical positive capital closure rule to have a positive and statistically as well as economically significant effect on individual firm growth - particularly for firms that are structurally more dependent on bank financing. Our findings are robust to various specifications. Investigating the transmission channels of the catharsis effect, we find that it essentially works through benefiting better quality firms and reallocating credit towards firms that need it most. Additional analyses suggest that the catharsis effect works best in open banking systems that provide high access to international finance and hence mitigate potentially negative credit supply effects of insolvent bank liquidation. Taken together, our findings advocate for stronger attention to incentive-compatible bank resolution regimes.
Keywords: G28; G21; K23; 330